2021
DOI: 10.1111/jcmm.16937
|View full text |Cite
|
Sign up to set email alerts
|

Aortic valve disease in diabetes: Molecular mechanisms and novel therapies

Abstract: Valve diseases and particularly calcific aortic valve disease (CAVD) and diabetes are progressive maladies and a global health burden for all aging societies. 1,2 Diabetic patients have a significantly greater propensity for cardiovascular disorders compared to non-diabetic individuals. [3][4][5] Accelerated CAVD is predictive of poor prognosis in valve disease and of faster degeneration of implanted bioprosthetic aortic valves. 6 Patients with diabetes mellitus (DM) not only have an amplified risk of CAVD but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 94 publications
(170 reference statements)
0
7
0
Order By: Relevance
“…Diabetes is a well-established risk factor of MAC, 19 and MAC can limit the dilation and the motion of mitral valve, which may lead to a low risk of severe MR. 13 Similarly, diabetes may also induce molecules calcification in aortic valve, 20 and inflammatory phenotype of valvular endothelial cells, which are associated with calcific aortic valve disease (CAVD). 21 CAVD may limit the dilation of the aortic root, which leads to the low risk of severe AR.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes is a well-established risk factor of MAC, 19 and MAC can limit the dilation and the motion of mitral valve, which may lead to a low risk of severe MR. 13 Similarly, diabetes may also induce molecules calcification in aortic valve, 20 and inflammatory phenotype of valvular endothelial cells, which are associated with calcific aortic valve disease (CAVD). 21 CAVD may limit the dilation of the aortic root, which leads to the low risk of severe AR.…”
Section: Discussionmentioning
confidence: 99%
“…This may bring some influences to the results. Studies have demonstrated that compared to than non-diabetic patients, patients diabetes showed a significantly elevated risk of CAVD, a significantly greater propensity for developing rapidly progressive AS, and a high degree of calcification in diseased aortic valves ( 65 , 66 ). This may explain the differences of diabetes between CAVD and control groups.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes can decrease the number and induce dysfunction of endothelial progenitor cells, impairing valve endothelial repair ( 30 ). Indeed, diabetes has been shown to be associated with aortic valve and bioprosthetic aortic valve degeneration ( 31 , 32 ). At the molecular level, diabetes can lead to the upregulation of biglycan, which may contribute to aortic valve degeneration ( 33 ).…”
Section: Discussionmentioning
confidence: 99%